(untitled) (International Journal of Scientific Trends, 2025)
This article analyzes the reforms being implemented in the field of property and entrepreneurship during the period of New Uzbekistan, the improvement of principles in this area, changes in legislation, and their impact on the economic and social environment. Attention is also paid to promising opportunities and existing problems in this area, and mechanisms for their elimination are proposed.